2014
DOI: 10.3892/or.2014.3274
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1 functions as a potential tumor suppressor in osteosarcoma by targeting Med1 and Med31

Abstract: MicroRNA-1 (miR-1) has been shown to function as a critical gene regulator in multiple types of cancers. However, the role of miR-1 in osteosarcoma has not been totally clarified. In the present study, we investigated the effects of miR-1 on osteosarcoma and the underlying mechanism. We found that miR-1 was downregulated in osteosarcoma tissues and osteosarcoma cell lines. Restoration of miR-1 significantly suppressed osteosarcoma cell proliferation by inhibiting cell cycle progression. Mediator complex subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…Overexpression of miR-1 has been shown to suppress cell proliferation in many cancers; the results of this study were consistent with these past studies (14,15,17). Previous studies have reported that miR-1 suppresses proliferation, migration, and invasion by down-regulating MET (11), Med1 and Med31 (18), and VEGFA (19) in osteosarcoma. Although some studies have reported that miR-1 induced cell-cycle arrest in the G 0 -G 1 phase by targeting MET, Med1 and Med31, a detailed analysis of the downstream genes related to the cell cycle has not been fully performed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overexpression of miR-1 has been shown to suppress cell proliferation in many cancers; the results of this study were consistent with these past studies (14,15,17). Previous studies have reported that miR-1 suppresses proliferation, migration, and invasion by down-regulating MET (11), Med1 and Med31 (18), and VEGFA (19) in osteosarcoma. Although some studies have reported that miR-1 induced cell-cycle arrest in the G 0 -G 1 phase by targeting MET, Med1 and Med31, a detailed analysis of the downstream genes related to the cell cycle has not been fully performed.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have reported that miR-1 suppresses proliferation, migration, and invasion by down-regulating MET (11), Med1 and Med31 (18), and VEGFA (19) in osteosarcoma. Although some studies have reported that miR-1 induces cell cycle arrest, a detailed analysis on downstream genes related to the cell cycle has not been fully performed, and evidence concerning the in vivo function of miR-1 has not been obtained.…”
mentioning
confidence: 99%
“…The 3′-UTR of MARCKS containing the putative miR-34c-3p binding sequence was amplified by PCR and cloned downstream of the firefly luciferase gene in the pMIR-Report vector (Promega Corporation, Madison, WI, USA) (12). Mutations in the miR-34c-3p seed regions of the MARCKS 3′UTR were generated using the QuikChang Multisite-directed mutagenesis kit (Promega Corporation).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in a screen for target genes, several miRs have been shown to regulate the expression of Mediator components in an embryonic stem cell line (Davis et al, 2012). Additionally, miR-146, miR-1, and miR-205 were shown to bind and regulate MED1 expression in spermatogonia, cancer cells, prostate cells, and trophoblasts, respectively (Hulf et al, 2013; Huszar and Payne, 2013; Jiang et al, 2014; Mouillet et al, 2010). Because MED1 seems to be regulated by multiple miRs, perhaps in a cell-specific manner, it will be important to determine the endogenous role of MED1 in these cell types.…”
Section: Questions For the Futurementioning
confidence: 99%